Extracurricular Vocational Training (1947-1989) - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 1993)
After the World War II, in secondary schools crafts were not taught but extracurricular work-linked training was gradually organized: young gardeners’, industrious hands, young technicians’ circles. Extracurricular activities accelerated even more after 1954-1955 m. when manual works have been included in the school curriculum again. The article discusses activity of technical circles. Here a lot of attention paid to regulation of extracurricular clubs for young technicians, which is reflected in the documents of Council of Ministers of the Lithuanian SSR, the Ministry of Education of the Lithuanian SSR and others. Also various regional and republican exhibitions of the creativity of young technicians are discussed. The paper analyses the problems met by such extra-curricular activities: sparse involvement into new circles, lack of motivation, lack of material base, etc.